You Are What You Eat, Microplastics in Porbeagle Sharks From the North East Atlantic: Method Development and Analysis in Spiral Valve Content and Tissue - Maes, Thomas; van Diemen de Jel, Jael; Vethaak, A. Dick; Desender, Marieke; Bendall, Victoria A.; van Velzen, Martin; Leslie, Heather A. (Frontiers in Marine Science, 2020)
Researchers worldwide are studying the environmental distribution and impacts of manufactured or environmentally fragmented small pieces of plastics, so called microplastics (<5 mm). These microplastics eventually build up in the marine environment, threatening marine ecosystems. The magnitude, fate and effects of these microplastics across the food web are largely unknown. Here, we measured digested microplastics in a top predator and critically endangered species, the North-East Atlantic Porbeagle shark (Lamna nasus), and compared this with general health conditions. A method for quantifying microplastics in spiral valves of porbeagle sharks was developed. Microplastics were detected in all spiral valves, up to 10.4 particles per g wet weight (w.w.) content and 9.5 particles per g w.w. tissue. This equates to individual microplastics loads as high as 3850 particles per spiral valve, most likely a result of trophic transfer. No statistically significant correlations were found between the average number of plastic particles in spiral valve content and tissue and the Condition and Hepatosomatic Index of porbeagle sharks. The results of this research show that North-East Atlantic porbeagle sharks ingest and digest microplastics and that there is a potential for microplastic biomonitoring using this species. More research is needed to detect possible health effects of microplastic contamination in these apex predators.